Risk Factors for Serious Prescription Opioid‐Related Toxicity or Overdose among Veterans Health Administration Patients. Issue 11 (14th June 2014) - Zedler, Barbara; Xie, Lin; Wang, Li; Joyce, Andrew; Vick, Catherine; Kariburyo, Furaha; Rajan, Pradeep; Baser, Onur; Murrelle, Lenn
Abstract Objective Prescription opioid use and deaths related to serious toxicity, including overdose, have increased dramatically in the United States since 1999. However, factors associated with serious opioid‐related respiratory or central nervous system (CNS) depression or overdose in medical users are not well characterized. The objective of this study was to examine the factors associated with serious toxicity in medical users of prescription opioids. Design Retrospective, nested, case‐control analysis of Veterans Health Administration (VHA) medical, pharmacy, and health care resource utilization administrative data. Subjects Patients dispensed an opioid by VHA between October 1, 2010 and September 30, 2012 (N = 8, 987). Methods Cases (N = 817) experienced life‐threatening opioid‐related respiratory/CNS depression or overdose. Ten controls were randomly assigned to each case (N = 8, 170). Logistic regression was used to examine associations with the outcome. Results The strongest associations were maximum prescribed daily morphine equivalent dose (MED) ≥ 100 mg (odds ratio [OR] = 4.1, 95% confidence interval [CI], 2.6–6.5), history of opioid dependence (OR = 3.9, 95% CI, 2.6–5.8), and hospitalization during the 6 months before the serious toxicity or overdose event (OR = 2.9, 95% CI, 2.3–3.6). Liver disease, extended‐release or long‐acting opioids, and daily MED of 20 mg or more were also significantly associated. Conclusions Substantial risk for serious opioid‐related toxicity and overdose exists at even relatively low maximum prescribed daily MED, especially in patients already vulnerable due to underlying demographic factors, comorbid conditions, and concomitant use of CNS depressant medications or substances. Screening patients for risk, providing education, and coprescribing naloxone for those at elevated risk may be effective at reducing serious opioid‐related respiratory/CNS depression and overdose in medical users of prescription opioids.